Toward an ethnohistory of Haitian pilgrimage - Terry Rey (Journal de la Société des Américanistes)
Toward an ethnohistory of Haitian pilgrimage. Combining historiography and ethnography, this article illustrates the various ethno-religious streams that have fertilized Haiti’s thriving pilgrimage traditions. With particular focus on the cults and feasts of St. James the Greater/Ogou Feray in La-Plaine-du-Nord and of St. Philomena/Lasyrenn in Bord-de-Mer-de-Limonade, and with a careful consideration of Kongolese religious culture (both Catholic and traditional), a convincing case is made here that pilgrimage in Haiti owes much more to Central African traditions than is generally acknowledged by scholars of Vodou, who over-emphasize the religion’s West African roots.